How state-reinforced knowledge infrastructure influences adaptive urban water governance - Aaron Deslatte; Jeffrey A Adams; Faisal S Cheema; Sara Alonso Vicario; Jesse L Barnes; Elizabeth A Koebele (Ecology and Society)
Resilience and environmental governance scholars have long studied and debated the role of the state in driving or coordinating responses to the varied dimensions of adaptive governance. In this study, we empirically analyze how multilevel, state-reinforced institutional designs impact the adaptive governance of urban water systems by structuring information production and use. Specifically, we analyze the multilevel institutional designs of “knowledge infrastructure systems,” defined as the rules and capacities within a system that allow actors to “produce, curate and communicate” information for governance. Drawing on a novel compilation of hydroclimatic data, media content, interviews, planning documents, and institutional designs, we empirically examine a typology of multi-level institutional arrangements in four U.S. urban water systems. Drawing from scholarship that considers the reflexivity of legal avenues and system performance, we conclude that state-reinforced rules governing the production and use of knowledge can clarify capacity-needs and support the efforts of managers responding to climate stressors through adaptive governance processes. They do so by formalizing planning types, timelines, and sanctions for noncompliance, while allowing local users and providers flexibility to innovate within these processes.